Water quality management in the food and beverage industry by hybrid automation using the example of breweries - Blomenhofer, Verena; Groß, Frauke; Procelewska, Joanna; Delgado, Antonio; Becher, Tobias (Water Science and Technology: Water Supply, 2013)
Water of drinking water quality is one of the most important resources in the food and beverage industry, e.g. for breweries. In this 'Water Quality Management' project, a new strategy of partial process water stream treatment is presented. Based on our own investigations, a water saving potential of 10-20% of the entire water consumption is possible with regard to displacement and rinsing water. The separation of different water qualities in real time, via the water switch, is achieved by several measurement techniques and the exploration of the desired information by multivariate data analysis. In combination with the water switch, the generation of drinking water quality regarding sterility is assured by a ceramic ultra-filtration membrane. Aside from basic on and inline measurement parameters in breweries, e.g. pH-value, temperature, electrical conductivity and turbidity, modern measurement techniques, e.g. infrared sensor, which can measure several parameters, such as Brix and organic acids, are utilized. The combination of the rule-based fuzzylogic system and expert knowledge is called a hybrid methodology. In the current study, the experimental design (DoE) techniques were applied to reduce the number of required experiments. The experimental results were then explored by the well-known projection method, i.e. principal component analysis (PCA). © IWA Publishing 2013.
UnivIS-Import:2015-04-14:Pub.2013.tech.ITC.stmmec.waterq
Keywords: Brewery; Fuzzy logic; Membrane filtration; Multivariate data analysis; Water treatment